An Antioxidant Enzyme Therapeutic for Sepsis - Li, Feifei; Yan, Ran; Wu, Jun; Han, Zeren; Qin, Meng; Liu, Chaoyong; Lu, Yunfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Sepsis is a systemic inflammatory response syndrome caused by infections that may lead to organ dysfunction with high mortality. With the rapid increase in the aging population and antimicrobial resistance, developing therapeutics for the treatment of sepsis has been an unmet medical need. Excessive production of reactive oxygen species (ROS) during inflammation is associated with the occurrence of sepsis. We report herein a treatment for sepsis based on PEGylated catalase, which can effectively break down hydrogen peroxide, a key component of ROS that is chemically stable and able to diffuse around the tissues and form downstream ROS. PEGylated catalase can effectively regulate cytokine production by activating leukocytes, suppress the elevated level of AST, ALT, TNF-α, and IL-6 in mice with induced sepsis, and significantly improve their survival rate.